2015
DOI: 10.1371/journal.pone.0146109
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of Remote Ischemic Conditioning Strategies on Recovery from Renal Ischemia-Reperfusion Injury and Protective Molecular Mediators

Abstract: Ischemia-reperfusion injury (IRI) is the major cause of acute kidney injury. Remote ischemic conditioning (rIC) performed as brief intermittent sub-lethal ischemia and reperfusion episodes in a distant organ may protect the kidney against IRI. Here we investigated the renal effects of rIC applied either prior to (remote ischemic preconditioning; rIPC) or during (remote ischemic perconditioning; rIPerC) sustained ischemic kidney injury in rats. The effects were evaluated as differences in creatinine clearance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Each animal underwent either right UNx or sham UNx, and was subjected to either 37 minutes of unilateral renal ischemia by left renal artery clamping or sham operation [ 30 ]. All operations were of similar total length.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each animal underwent either right UNx or sham UNx, and was subjected to either 37 minutes of unilateral renal ischemia by left renal artery clamping or sham operation [ 30 ]. All operations were of similar total length.…”
Section: Methodsmentioning
confidence: 99%
“…First, the right-sided nephrectomy or sham procedure was performed. Next, the left renal artery was carefully dissected, and a non-traumatic microvascular clamp was used to occlude the artery to induce 37 minutes of warm ischemia [ 30 ]. The sham ischemia procedure involved visual identification of the left renal hilus.…”
Section: Methodsmentioning
confidence: 99%
“…It is also expected that the RIR injury induced inflammation may increase KW as Afyouni and colleagues demonstrated that KW increased in RIR injury model (19). A model of IPC, in which bilateral renal pedicles were clipped for 5 min followed by 5 min reperfusion for three times, resulted in an improvement of renal injury (20). Such improvement was not obtained in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Also, proteomic analysis of plasma in RIC models found measureable changes of the acute inflammatory response [ 11 , 12 ]. At the same time, mixed results have been observed, revealing no difference in levels of tubular damage caused by IRI after combined or separate pre- and post-conditioning [ 6 , 13 , 14 ]. More recently, the results of a randomised clinical trial in kidney transplantation (CONTEXT) were reported, applying RIC (preconditioning) to recipients of deceased donor kidneys.…”
Section: Introductionmentioning
confidence: 99%